Data-driven calibration for infrared camera in additive manufacturing. (27th June 2019) - Francis, Jack; Khanzadeh, Mojtaba; Doude, Haley; Hammond, Vincent; Bian, Linkan
Non-contact infrared (IR) measurement devices are currently used to monitor the thermo-physical processes during additive manufacturing (AM). A common IR device for thermal monitoring, the IR camera, requires a blackbody calibration in order to be used effectively, as the camera measures the radiant energy (irradiance) instead of the true temperature. This calibration is difficult, expensive, and requires specialised equipment. Therefore, this article details a data-driven calibration for IR cameras by comparing the lengths of cutoff regions captured by the pyrometer and IR camera. After scaling and interpolating pyrometer images, a similarity metric is developed that characterises the relationship between irradiance and temperature. An application of the IR camera for monitoring thermo-physical processes is discussed in detail.